(untitled) (LIS TODAY, 2023)
The goal of this paper is to see if it is possible to incorporate chat GPT applications into library reference services. This paper provides an overview of the Chat GPT application, which is being integrated into library services to provide users with ready reference and current awareness services. The paper discusses the role of the reference librarian in the age of chat GPT, such as user guidance and content creation. The advantages of chat GPT were identified, such as improving search and discovery, database development, cataloguing, and content creation, and providing a 24/7 current awareness service, which meets a demand that librarians are sometimes unable to meet. Chat GPT issues such as confidentiality and bias, availability issues, and accuracy issues were also discussed. There were suggestions offered to enhance the chat GTP service.